Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Schmidt, Jörn O.; Bograd, Steven J.; Arrizabalaga, Haritz; Azevedo, José L.; Barbeaux, Steven J.; Barth, John A.; Boyer, Tim; Brodie, Stephanie; Cárdenas, Juan José; Cross, Scott; Druon, Jean-Noël; Fransson, Agneta; et al. (Frontiers in Marine Science, 2019)
Advances in ocean observing technologies and modeling provide the capacity to revolutionize the management of living marine resources. While traditional fisheries management approaches like single-species stock assessments are still common, a global effort is underway to adopt ecosystem-based fisheries management (EBFM) approaches. These consider changes in the physical environment and interactions between ecosystem elements, including human uses, holistically. For example, integrated ecosystem assessments aim to synthesize a suite of observations (physical, biological, socioeconomic) and modeling platforms (ocean circulation models, ecological models, short-term forecasts, management strategy evaluations) to assess the current status and recent and future trends of ecosystem components. This information provides guidance for better management strategies. A common thread in EBFM approaches is the need for high-quality observations of ocean conditions, at scales that resolve critical physical-biological processes and are timely for management needs. Here we explore options for a future observing system that meets the needs of EBFM by i) identifying observing needs for different user groups, ii) reviewing relevant datasets and existing technologies, iii) showcasing regional case studies, and iv) recommending observational approaches required to implement EBFM. We recommend linking ocean observing within the context of GOOS and other regional ocean observing efforts with fisheries observations, new forecasting methods, and capacity development, in a comprehensive ocean observing framework.